Analysis of The Legal Status of Gig Workers in Indonesia’s Digital Platforms: The Urgency of Sufficient Work Regulations as Social Protection - Christopher Panal Lumban Gaol; Bambang Eko Nugroho; Dadang Sumarna; Asnal Hafiz; Irsan Rahman (Inovasi Pratama Internasional. Ltd, 2026)
The rapid expansion of Indonesia's digital economy has created approximately 41.6 million gig workers, yet their legal status remains undefined within the existing labor law framework. This study employs quantitative and normative legal analysis to examine the legal status of gig workers operating through digital platforms (Gojek, Grab, and other service applications) and evaluate the adequacy of current Indonesian labor regulations in providing social protection. Through analysis of statutory instruments including Law No. 13 of 2003 on Manpower and Law No. 11 of 2020 on Job Creation (Omnibus Law), alongside empirical data on worker demographics, income distribution, and social security participation rates, this research demonstrates that gig workers meet substantive criteria of employment yet remain classified as independent contractors. The study reveals that 7.61 percent of informal workers maintain social security coverage, with participation rates as low as 1.6 percent among gig workers specifically. Quantitative analysis of 130 gig workers across three provinces demonstrates income volatility (average monthly earnings: IDR 3.0-3.98 million), excessive working hours (30-40 hours weekly, with 20 percent exceeding 40 hours), and negligible social safety net access (49.23 percent lack health insurance). The research concludes that the Sufficient of Work doctrine, grounded in ILO conventions and the principle of decent work, provides a superior analytical framework for protecting digital platform workers. The study recommends legislative reform incorporating hybrid employment categories, mandatory social protection coverage regardless of classification, and algorithmic transparency mechanisms as essential safeguards for worker dignity and economic security in Indonesia's evolving labor market